2021
DOI: 10.1007/s00268-021-06201-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy has A Positive Impact on Subclinical Hypothyroidism Among Obese Patients: A Prospective Study

Abstract: Background The effect of bariatric surgery on postoperative thyroid function remains incompletely understood. In this study, we aimed to evaluate the changes in thyroid functions after gastric sleeve operation for morbidly obese Egyptian patients. Methods This was a prospective study that recruited 128 patients who underwent sleeve gastrectomy through the period from December 2016 to April 2020. We measured thyroid-stimulating hormone (TSH), free thyroxin (FT4), and free triiodothyronine. Subclinical hypothyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Female patients with higher preoperative TSH levels achieved better weight-loss outcomes. Clinical studies have demonstrated a positive correlation between obesity and plasma TSH levels ( 32 , 33 ). A previous study initially reported that the TSH level decreased significantly after SG in euthyroid patients.…”
Section: Discussionmentioning
confidence: 99%
“…Female patients with higher preoperative TSH levels achieved better weight-loss outcomes. Clinical studies have demonstrated a positive correlation between obesity and plasma TSH levels ( 32 , 33 ). A previous study initially reported that the TSH level decreased significantly after SG in euthyroid patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, changes in thyroid-stimulating hormone (TSH) after bariatric surgery reported by different studies varied dramatically. TSH levels were found to decline significantly following bariatric surgery in the majority of studies involving patients with subclinical or overt hypothyroidism ( 10 12 ). Similar results have been noted in a number of researches involving patients with normal thyroid function ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dysfunction of the TH/TR axis leads to numerous pathologies, especially including growth, skeletal development, heart diseases, cognitive dissonance, gastrointestinal function, obesity, dysmetabolism, and cancers ( Brent, 2012 ; Ortiga-Carvalho et al, 2014 ; Ajdukovic et al, 2021 ; Moutzouri et al, 2021 ; Niedowicz et al, 2021 ; Salman et al, 2021 ). Therefore, the abnormity of the TH/TR axis elicits a series of diseases, the most common of which is metabolic disease ( Malm, 2004 ).…”
Section: Introductionmentioning
confidence: 99%